A study on the catalytic activity of polypeptides toward the hydrolysis of glucoside compounds gastrodin, polydatin and esculin. Issue 47 (28th November 2022) - Hou, Juan; Lei, Xiangmin; Liu, Borui; Wang, Zejiang; Fang, Guozhen; Liu, Jifeng; Wang, Shuo
Abstract : A series of catalytically active self-assembled polypeptide materials for the hydrolysis of glucoside compounds ( e.g., gastrodin, polydatin and esculin) were investigated. Abstract : The self-assembly of a series of catalytically active polypeptides toward hydrolysis of glucoside compounds, namely, gastrodin, polydatin and esculin was investigated. These active peptides are composed of two functional fragments: one is the hydrophobic sequence LHLHLRL, which forms assembling segments in the presence of Zn ions (Zn 2+ ); another functional sequence of active peptides are catalytic sites such as Glu (E), Asp (D) and His (H), where carboxylic acids (–COOH) or imidazole groups act like scissors to cleave glucoside bonds of the compounds (according to the acid–base coupling mechanism). The effects of the amino acid sequence of the peptide, Zn 2+ concentration, pH and the size or steric hindrance of glucoside compounds on the hydrolytic activity were studied. It was found that the crystalline structure of assembled peptides was crucial to provide the peptide with catalytic hydrolytic activity. Noncovalent interaction index was used to analyse the noncovalent interaction of PEs with glucoside compounds, including hydrogen bonds, van der Waals, and steric effect in the complexes. The binding energy of complexes, the direction and site of nucleophilic attack during deglycosylation processes were also investigated by molecular docking and the electron density Laplace function. This revealed that the differences in the hydrolytic activity of peptides toward glucoside compounds with different sizes originated from different hydrogen bond interactions between the peptides and substrates. These active peptides may find application in the preparation of drugs by de-glycosylation of natural compounds.